Full-genome next-generation sequencing of hepatitis C virus to assess the accuracy of genotyping by the commercial assay LiPA and the prevalence of resistance-associated substitutions in a Belgian cohort - Christensen, Kasper T. (2022)
Funding Information: This work and KTC were supported by grants from the Fonds voor Wetenschappelijk Onderzoek Vlaanderen (FWO) ( G069214 , G0B2317N , 1S38819N ). LC acknowledges FWO travel grant for a research visit at University of Oxford ( V431117N ). The authors thank the staff in Oxford in their support of the laboratory work and the donation of the probes used for enrichment of HCV. Publisher Copyright: © 2022 Elsevier B.V.